MONETARY POLICY: REGULATORY NEWS AND CHANGE IN THE MOVEMENT OF FINANCIAL FLOWS - V. V. Korneev; А. A. Khodzhaian; Yu. Yu. Vergeluk; Yu. V. Koverninska (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
The article deals with the issues of formation and implementation of monetary policy. The peculiarities of implementation of monetary regime of inflation targeting in Ukraine and in other countries are defined.